BLACK WOMAN’S SOLITUDE: : A HISTORY OF AFFECTIVE INVISIBILITY - Mirella Rodrigues da Cruz (Revista Gênero e Interdisciplinaridade, 2021)
This article aims to show an analysis of the book Kired, Laços deangue, by Octavia E. Butler, under the perspective of observing the aspects that permeate the dynamics of affectivity, from the dialogue used in racial disparities, with a view to conditioning social that determines our loving inclinations, established through a historical and racial point of view, which makes black women unfeasible as active individuals in affective spaces.